Penerapan Konsep Hybrid Contracts dalam Pembiayaan Rahn di Pegadaian Syariah - M, Faruqi Imam; Abdal, Abdal; Arifin, Tajul (AHKAM, 2024)
Islamic financing has become an increasingly popular option for individuals and businesses looking to meet their financial needs in accordance with Islamic principles. One of the prominent innovations in Islamic financing is the concept of Hybrid Contracts, which allows combining several types of Islamic contracts in one financing product. This article explores the role and benefits of the concept of Hybrid Contracts in financing rahn at Pegadaian Syariah. We also explain the detailed implementation steps, which include customer identification, risk evaluation, determination of sharia contract type, application submission, feasibility review, contract signing, transaction execution, and financing monitoring. The concept of Hybrid Contracts helps increase flexibility, inclusivity, and compliance with sharia principles in rahn financing, opening the door to broader sharia-based economic development.